Experimental and validation of glass-ceramic composite properties derived from waste materials at elevated sintering temperature - Shamsudin, Zurina; Mesri, Masturah; Mohamad Dom, Adibah Haneem; Hasan, Rafidah; Mulyadi, Mahmud (Penerbit Universiti Teknikal Malaysia Melaka, 2023)
The glass-ceramic composite (GCC) from waste material has limited performance especially strength properties that can be improved by reinforced with filler under sintering temperature controlled which commonly used in two steps sintering process. In this study, the influence of elevated sintering temperature using single step or direct sintering process on mechanical properties and microstructural analysis of GCC at various filler loadings were investigated and assessed. The GCC was prepared using eggshell (ES), spent bleach earth (SBE) and soda lime silicate glass (SLSG). Eggshell acted as filler was calcined at temperature of 1000 °C before sintered to direct sintering process. This combination was aimed to improve the performance of GCC by controlling the sintering temperature. The sample was sintered at four types of sintering temperatures at 750, 800, 850 and 900 °C using 2 °C/min heating rate with constant holding time. The GCC was formed with the inclusion of eggshell at 0, 5, 10, and 15 wt% as filler. The performance of GCC was analysed through mechanical testing while microstructure of the samples was characterized by using Field emission scanning electron microscopy (FESEM). The results revealed the average of Vickers Micro-hardness and flexural strength was a function of sintering temperature and filler loading. The analyses from these results were indicating that it is possible to produce a good GCC using local waste contributed by 15% of eggshell with the highest value of micro-hardness (1011.64 HV) and with highest flexural strength (54.82 MPa) obtained. Validation via fractography analysis indicated, at high content of filler, the microstructure was more densified as number of pores was minimized. These findings concluded that the suitable sintering temperature can be controlled for alternative materials for structural applications.